THE ACADEME IN THE GLOBAL AND DIGITAL AGE: THE PLACE OF LITERATURE TODAY - Wilke, Sabine (Literatūra, 2016)
This paper engages with the scholarly discussion of the process of globalization and how they relates to changes in our discipline. The first problem is the fact that most of the scholarly literature on globalization originates from the social sciences and it is unclear how this body of scholarship transfers to what we are doing, i.e., how it relates to aesthetic issues and the understanding and critique of cultural practices. It is one thing to describe the portrayal of contemporary culture with its emphasis on consumer goods and material processes of exchange in contemporary literary texts, thematically so to speak, and it is quite another to engage with the concept of globalization on a structural level. What does a discipline of literary and cultural studies look like that has a refined understanding and critical engagement with globalization as a process that characterizes contemporary societies worldwide, not one that is simply borrowed from the social sciences and then tested on literary texts? What are the main topics of such a newly realigned discipline and what are its methodological premises? German Studies in a globalized age is an endeavor that highlights the negotiation of cultural values on a local level in a global context. Literary and cultural studies in a global age should focus on what they do best, i.e., describe the functioning of aesthetic structures. The national literatures need to shift their focus from a nationalist philological agenda to a more global arena, not to be confused with traditional comparative literature that presumes the existence of different nationalist agendas that then can be compared. Literary and cultural studies in a global and digital age must be expansive and situate its regional focus within global concerns on a thematic as well as a structural level.